A berberine-loaded hydrogel for the treatment of atopic dermatitis through antibacterial activity, inhibition of inflammation and modulation of oxidative stress - Peng, Ze; Wei, Xin-Yu; Zeng, Xin; anwaier, Gulinigaer; Zhou, Xun; Shi, Bing-Jun (Frontiers in Immunology, 2026)
BackgroundAtopic dermatitis (AD) is a chronic, pruritic, immune-mediated inflammatory skin disorder characterized by Th2-dominant immune response, which may contribute to systemic inflammation. Hydrogels, as drug delivery vehicles, demonstrate excellent biocompatibility and superior moisturizing capabilities. Berberine exhibits anti-inflammatory, antibacterial, and immunomodulatory properties. However, the therapeutic efficacy and underlying mechanisms of berberine-loaded hydrogel (BHG) in the management of AD remain insufficiently elucidated.MethodsThe morphology and structure of the hydrogel were examined using scanning electron microscopy. In vitro biocompatibility of the BHG was assessed via the CCK-8 assay and hemolysis testing. In vivo, an AD model was induced in mice by topical application of DNFB to the shaved dorsal skin. Clinical symptoms, including erythema, edema, and crusting, were monitored, and serum levels of IL-4, IL-13, IgE, and histamine were quantified using ELISA. H&E staining was performed to evaluate epidermal and dermal thickness, while toluidine blue staining was employed to assess mast cell infiltration in the dermis. Immunohistochemical staining was conducted to examine the expression of skin barrier-related proteins, and immunofluorescence staining was utilized to detect reactive oxygen species (ROS) levels in skin tissues. The expression levels of PI3K, AKT, and NF-κB pathway proteins were analyzed by Western blotting.ResultsThe BHG exhibited no adverse effect on HaCaT cell viability and demonstrated effective inhibition of Staphylococcus aureus proliferation. It significantly alleviated dermatological symptoms in AD mice, including erythema, edema, and crusting, while reducing scratching frequency, epidermal thickness, and mast cell infiltration. The formulation suppressed the expression of Th2-associated cytokines, including IL-4, IL-13, TNF-α, IL-6, and IgE. In the dorsal skin of AD mice, the BHG reduced levels of ROS and malondialdehyde (MDA), while increasing superoxide dismutase (SOD) activity. Furthermore, it enhanced the expression of skin barrier proteins such as filaggrin, occludin, and ZO-1, and downregulated the expression of phosphorylated PI3K, AKT, and NF-κB (p-PI3K, p-AKT, and p-NF-κB) proteins.ConclusionThe BHG exhibits favorable biocompatibility and potent antibacterial activity, and is capable of restoring the skin barrier and ameliorating dermatological symptoms in AD mice. Its anti-inflammatory and antioxidant effects may be mediated through modulation of the PI3K/AKT/NF-κB signaling pathway.